2010
DOI: 10.1111/j.1365-3164.2010.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Stratum corneum removal facilitates experimental sensitization to mite allergens in atopic dogs

Abstract: In humans with atopic dermatitis and in mouse models of IgE-mediated allergic diseases, evidence is mounting that the stratum corneum (SC) provides an important barrier against environmental allergens. At this time, it is not known whether the SC has a similar role in dogs, especially in those with atopic dermatitis. The objectives of this pilot study were to determine whether SC removal led to earlier and stronger sensitization of atopic dogs to Dermatophagoides farinae (Df) house dust mites. Five Maltese-bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 49 publications
1
38
0
1
Order By: Relevance
“…Corneodesmosin, as it covers lower SC desmosomes, prevents their early proteolytic digestion by proteases released from lamellar bodies in the upper stratum granulosum; this function of CDSN prevents an early SC desquamation . Given that SC removal facilitates allergen sensitization in dogs as in other species, the HDM‐associated degradation of CDSN staining could, hypothetically, lead to an early SC desquamation and secondarily increase allergen penetration and development of sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Corneodesmosin, as it covers lower SC desmosomes, prevents their early proteolytic digestion by proteases released from lamellar bodies in the upper stratum granulosum; this function of CDSN prevents an early SC desquamation . Given that SC removal facilitates allergen sensitization in dogs as in other species, the HDM‐associated degradation of CDSN staining could, hypothetically, lead to an early SC desquamation and secondarily increase allergen penetration and development of sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…We also included sera from 15 laboratory dogs (six beagles, nine Maltese‐beagle atopic dogs) sensitized to Df HDM by repeated epicutaneous application of lyophilized ground mites . In all of these dogs, hypersensitivity to this allergen had been confirmed beforehand by positive allergen specific intradermal testing (IDT) and/or IgE serology done at regional commercial laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Olivry et al. 17 reported that performing TS in atopic dogs removed the SC and facilitated experimental sensitization to mite allergens. Finally, Ohmori et al.…”
Section: Introductionmentioning
confidence: 99%